Analisis Kebijakan dalam Ranperda Sistem Pendidikan Kabupaten Lamongan - Madekhan Madekhan (Reforma : Jurnal Pendidikan dan Pembelajaran, 2017)
This article focus on analysis of educational policy, especially dealt with draft of District Regulation (Ranperda) on Adjusting of  Lamongan District Regulation No. 30/2007 About Educational System. Through empirical analysis in several aspects of sociology, public service, and governance, the article provide  management approach in term of 3P Formula in enhancing the effectiveness of educational policy performance in Lamongan. On the basis of such analysis, the article go to recommendation that the effectiveness of District Regulation (Ranperda) will depend on; first, how well the draft of District Regulation (Ranperda) formulated in manner of the high initiatives of stakeholders. Second, how the process of formulation District Regulation (Perda) adopt the principle of marginal community advocacy. The third is on how the implementation of District Regulation (Perda) follow the principles of good governance.Keywords: Education Policy, District Regulation